Majusia55
Rozwiązane

5x+3y=0
-x-2y=7
____________



Odpowiedź :

5x+3y=0
-x-2y=7

-x-2y=7
x=-2y-7

5x+3y=0
5(-2y-7)+3y=0
3y-10y-35=0
-7y=35
y=-5

x=-2y-7
x=-2*(-5)-7
x=10-7
x=3

odp. x=3; y=-5
5x + 3y = 0 / - (3y)
-x - 2y = 7

5x = 3y / ÷ 5
-x - 2y = 7

x = 3y/5 (trzy y nad pięć
-x - 2y = 7

x = 3y/5
-(3y/5) - 2y = 7

x = 3y/5
-3y/5 - 2y = 7 / ×5

x = 3y/5
-3y - 2y = 35

x = 3y/5
-5y = 35 / ÷ (-5)

x = 3y/5
y = - 7

x= 3 × (-7)/5
y = -7

x = (-21)/5
y = -7

x = -4,2
y = -7
5x+3y=0
-x-2y=7 /*(-1)

5x+3y=0
x+2y+-7

5x+3y=0
x=-7-2y
5(-7-2y)+3y=0
-35-10y+3y=0
-35-7y=0
7y=-35 /:7
y=-5

5x+3*(-5)=0
5x-15=0
5x=15 /:5
x=3

x=3
y=-5